Elevated glucose promotes generation of endothelium-derived vasoconstrictor prostanoids in rabbit aorta. - Tesfamariam, B (1990)
The effects of glucose on endothelium-dependent responses and vasoactive prostanoid production were determined by incubating isolated rabbit aortae in control (5.5 or 11 mM) or elevated (44 mM) glucose for 6 h to mimic euglycemic and hyperglycemic conditions. Rings of aortae incubated in elevated glucose, contracted submaximally by phenylephrine, showed significantly decreased endothelium-dependent relaxations induced by acetylcholine compared with the aortae incubated in control glucose. Treatment with indomethacin, a cyclooxygenase inhibitor, or SQ29548, a prostaglandin H2/thromboxane A2 receptor antagonist, restored acetylcholine relaxations of rings in elevated glucose to normal, while these agents had no effect on the relaxation of rings incubated in control glucose. Aortae incubated with mannose (44 mM) as a hyperosmotic control relaxed to acetylcholine normally. The relaxations in response to A23187 and sodium nitroprusside were not different between rings exposed to control and elevated glucose. Radioimmunoassay measurements showed a significant increase in acetylcholine-stimulated release of thromboxane A2 and prostaglandin F2 alpha in aortae with, but not without endothelium incubated with elevated, but not with control glucose. Thus a possible mechanism for endothelium dysfunction in diabetes mellitus is the hyperglycemia-induced increased generation of endothelium-derived vasoconstrictor prostanoids.